Galactic bar resonances inferred from kinematically hot stars in Gaia EDR3. Issue 1 (16th September 2021) - Kawata, Daisuke; Baba, Junichi; Hunt, Jason A S; Schönrich, Ralph; Ciucă, Ioana; Friske, Jennifer; Seabroke, George; Cropper, Mark
ABSTRACT: Using a numerical simulation of an isolated barred disc galaxy, we first demonstrate that the resonances of the inner bar structure induce more prominent features in the action space distribution for the kinematically hotter stars, which are less sensitive to the local perturbation, such as the transient spiral arms. Then, we analyse the action distribution for the kinematically hotter stars selected from the Gaia EDR3 data as the stars with higher values of radial and vertical actions. We find several resonance features, including two new features, in the angular momentum distribution similar to what are seen in our numerical simulations. We show that the bar pattern speeds of about Ωbar ∼ 34 and 42 km s −1 kpc −1 explain all these features equally well. The resonance features we find correspond to the inner 4:1, co-rotation (CR), outer 4:1, outer Lindblad, and outer 4:3 (CR, outer 4:1, outer Lindblad, outer 4:3, and outer 1:1) resonances, when Ωbar ∼ 34 (42) km s −1 kpc −1 is assumed.